2004
DOI: 10.1007/s00018-004-4030-2
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone receptors A and B differentially modulate corticotropin-releasing hormone gene expression through a cAMP regulatory element

Abstract: Corticotrophin-releasing hormone (CRH) plays a major role in mechanisms controlling human pregnancy and parturition. Gene regulation by progesterone may be a key point in the control of placental CRH production. Studies in primary placental cells show that antagonism of progesterone activity or production by RU486 or trilostane leads to an increase in CRH promoter activity. This effect can be reversed by the addition of progesterone. Overexpression of progesterone receptor A (PR-A) or glucocorticoid receptor r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 44 publications
1
23
0
1
Order By: Relevance
“…While PR-A is associated with progesterone-induced COMT upregulation, PR-B is associated with downregulation of COMT expression. The distinctive effect of PR-B and PR-A on COMT expression is consistent with other observations that PR-A and PR-B have an opposing effect on the expression of many genes [37][38][39][40]. The underpinning mechanism of the distinct activities of PR-A and PR-B in gene expression is not well understood, although it has been shown that distinct coregulator recruitment and usage are involved at some levels [41].…”
Section: Discussionsupporting
confidence: 88%
“…While PR-A is associated with progesterone-induced COMT upregulation, PR-B is associated with downregulation of COMT expression. The distinctive effect of PR-B and PR-A on COMT expression is consistent with other observations that PR-A and PR-B have an opposing effect on the expression of many genes [37][38][39][40]. The underpinning mechanism of the distinct activities of PR-A and PR-B in gene expression is not well understood, although it has been shown that distinct coregulator recruitment and usage are involved at some levels [41].…”
Section: Discussionsupporting
confidence: 88%
“…For example, progesterone can stimulate JNK activation both through the MEK/p42 MAPK pathway and MEK/p42 MAPK-independent pathways in Xenopus oocytes (Bagowski et al, 2001). Ni and co-workers reported that progesterone regulates CRH gene transcription via a cAMP regulatory element in the CRH promoter (Ni et al, 2004). Recently, the human membrane progesterone receptor (Jang and Yi, 2005) and receptor gene were identified (Bernauer et al, 2001).…”
Section: Introductionmentioning
confidence: 98%
“…Both isoforms share an identical ligand-binding domain, which includes an activation function. The PGRA and PGRB can be considered as two independent receptors that display different transcriptional activities [16,17]. It has been described that a different set of genes is regulated by progesterone in cells that express different PGR isoform profiles [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%